EVALUASI PROGRAM PENGGUNAAN HELM KESELAMATAN DI PROYEK KONSTRUKSI - Maret Jerman Samosir (Kohesi: Jurnal Sains dan Teknologi, 2025)
Construction projects are one of the jobs that have high risk in the field, especially in Indonesia today. The use of construction helmet Personal Protective Equipment (PPE) by workers is mandatory. Planning a helmet use program in construction projects is one of the mostvital to protect the head. With the planning of a helmet use program as one of the Occupational Safety and Health (K3) in contruction project, it it hoped that various work accidents that can occur to all workers in construction cab be avoided.